2016
DOI: 10.1242/jeb.142331
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral bending mechanics and xenarthrous morphology in the nine-banded armadillo (Dasypus novemcinctus)

Abstract: The vertebral column has evolved to accommodate the broad range of locomotor pressures found across vertebrate lineages. Xenarthran (armadillos, sloths and anteaters) vertebral columns are characterized by xenarthrous articulations, novel intervertebral articulations located in the posterior trunk that are hypothesized to stiffen the vertebral column to facilitate digging. To determine the degree to which xenarthrous articulations impact vertebral movement, we passively measured compliance and range of motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 42 publications
3
45
0
Order By: Relevance
“…Other researchers have found that long centra allow more dorsiflexion and sometimes lateroflexion [6973]. Turkeys do not appear to follow either of these patterns: centrum length increases from C3 to C7, then plateaus (Fig.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Other researchers have found that long centra allow more dorsiflexion and sometimes lateroflexion [6973]. Turkeys do not appear to follow either of these patterns: centrum length increases from C3 to C7, then plateaus (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…6 and 10). Centrum width has been reported to restrict lateroflexion [18, 73, 74] while zygapophyseal width has been reported to restrict torsion [69]. Again, neither morphological trend matches the mobility trends in turkeys (Figs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to Gray (), the tripod gait (i.e., three‐legged support of ground locomotion) for lateral sequences provides more stability when compared to diagonal sequences. This kind of gait would favour the undulation of the spine in many tetrapods (e.g., salamanders) (Gray, ), but although armadillos have developed the mechanical capacity of ventroflexing their columns (e.g., Tolypeutes Illiger, 1811), there is a significant lateral stiffness—that could be attributable to xenarthrae (Gaudin & Biewener, ; Oliver et al., ). Indeed, the dorsoventral degree of mobility in the mammalian vertebral column is directly related to locomotor function, which would reflect different patterns of flexion/extension of joints (Molnar, Pierce, & Hutchinson, ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of an armoured carapace, for example, as a feature for all cingulates, has been related to a relatively slow plantigrade locomotion in other mammals (Superina & Loughry, ), but no data have been provided to confirm this pattern in armadillos. Moreover, the presence of xenarthrous vertebrae adds a quite original peculiarity to this design, and as these elements provide the stiffening of the vertebral column they are also related to locomotion in the sense that the stability thus provided would allow these animals to bend (Oliver, Jones, Hautier, Loughry, & Pierce, ).…”
Section: Introductionmentioning
confidence: 99%